Современные методы повышения эффективности парогазовых установок - Беляева, С. О.; Коваль, В. А. (НТУ "ХПИ", 2008)
The possibility of a raise of effectiveness stem-gas an engine installation due to rational injection of water in the setting of the axial-flow compressor is considered. Experimentally effect of injection of water in different places its input in the compressor is explored at various operational modes and rotational displacement of stators.
Keywords: ГТД; удельная мощность; КПД; тепловая эффективность; газопаровые циклы; впрыск воды в компрессор